2022
DOI: 10.3390/app12147343
|View full text |Cite
|
Sign up to set email alerts
|

Physical Development Differences between Professional Soccer Players from Different Competitive Levels

Abstract: In soccer, physical development is crucial for developing optimal performance. This study aimed to assess and compare the physical development of elite and non-elite professional soccer players. Seventy-eight male professional football players divided into four competitive levels participated in this study: the elite group (EG), the non-elite group A (NEG-A), the non-elite group B (NEG-B), and the under 23 group (U23). Body composition, static strength, lower-body explosive strength, flexibility, and balance w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…When comparing the performance levels, the results showed that, although there were no statistical differences between both groups AL, high-level athletes suffered significantly higher numbers of injuries BL than amateur athletes. This may arise from the greater demands in training and competitions faced by high-level athletes [49], caused by higher internal (i.e., psychophysiological responses of the athletes that take place during an exercise) and external loads (i.e., loads prescribed by the coach to elicit psychophysiological responses) compared to amateur athletes [16,50]. Although several studies have shown significant increases in the number of injuries in high-level athletes, mainly due to the abrupt increase in the training load after returning to competition and the greater concentration of competitions in a short period of time [3,10,39,43,[51][52][53], other studies have shown that changes in IRs did not significantly increase AL in high-level athletes [12,46], thanks to individualized work during this time.…”
Section: Discussionmentioning
confidence: 99%
“…When comparing the performance levels, the results showed that, although there were no statistical differences between both groups AL, high-level athletes suffered significantly higher numbers of injuries BL than amateur athletes. This may arise from the greater demands in training and competitions faced by high-level athletes [49], caused by higher internal (i.e., psychophysiological responses of the athletes that take place during an exercise) and external loads (i.e., loads prescribed by the coach to elicit psychophysiological responses) compared to amateur athletes [16,50]. Although several studies have shown significant increases in the number of injuries in high-level athletes, mainly due to the abrupt increase in the training load after returning to competition and the greater concentration of competitions in a short period of time [3,10,39,43,[51][52][53], other studies have shown that changes in IRs did not significantly increase AL in high-level athletes [12,46], thanks to individualized work during this time.…”
Section: Discussionmentioning
confidence: 99%
“…However, in contradiction, some studies have found sub-elite soccer players to be of greater stature than their elite counterparts, suggesting that stature may not always characterize elite status or performance (6). Sports performance research has yet to fully define main attributes and actions that differentiate successful soccer players from unsuccessful soccer players (7)(8)(9)(10)(11)(12)(13). Limited research has been done assessing what constitutes match-playing time in soccer and why some players receive more playing time than others.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of physical attributes of individuals competing at different levels has shown significant differences between elite players and their lower-division peers in body composition (França et al, 2022;Mala et al, 2023), and several strength indicators (Cometti et al, 2001;França et al, 2022;Śliwowski et al, 2017). Regarding isokinetic assessment, KF PT and the H:Q ratio were significantly greater in international soccer players compared to noninternational ones (Śliwowski et al, 2017).…”
Section: Discussionmentioning
confidence: 99%